The Seventh EU Enlargement and Beyond: Pre-Accession Policy vis-à-vis the Western Balkans Revisited - Mirna Vlašić Feketija; Adam Lazowski (Croatian Yearbook of European Law and Policy, 2014)
The accession of Croatia to the European Union is yet another milestone in the history of EU enlargements. After seven enlargement rounds the membership has increased from the original six founding countries to twenty-eight Member States. Many claim, quite rightly, that the enlargement policy is the most successful of the EU’s foreign policy tools. Even those who bring this bold argument into doubt have to agree that, when contrasted with other external policies, and the European Neighbourhood Policy in particular, the overall balance sheet of the enlargement policy is positive. The accession of Croatia is symbolic in a number of ways. As argued in this article, it closes one big chapter in the history of EU enlargements but, at the same time, opens another. Croatia is – most likely – the last country to join the EU this decade. After a sometimes painful pre-accession process, it has proved to be a ‘success story’ of the stabilisation and association process. As the European Commission claims, it is living proof that the raison d’être and mechanics of the policy employed vis-à-vis the Western Balkans have their merits. However, a quick look into the future proves that the next enlargements will be far more complicated affairs. The current list of candidates and potential candidates is a mix of a heavyweight (Turkey) and the Western Balkan countries, all struggling to meet the fundamental prerequisites for a democracy based on the rule of law. Failure to comply with the Copenhagen criteria, together with a dwindling appetite for further enlargement among some Member States, create a rather dangerous mix. This article argues that following recent enhancements to the pre-accession policy, further improvements are necessary to make future expansions of the European Union possible. If only from the geopolitical perspective, this is in the joint interest of the European Union, its Member States and the countries of the Western Balkans.